Perbedaan Jumlah Trombosit Menggunakan Antikoagulan K3EDTA dengan Volume Sampel Berbeda pada Karyawan Puskesmas Wanadadi 1 Kab. Banjarnegara - Wahyu Hidayah; Tantri Analisawati Sudarsono; Linda Wijayanti; Retno Sulistiyowati (CV. Ulil Albab Corp, 2022)
Platelets (thrombocytes) form a mechanical blockage to the hemostatic response to burns through several reactions, adhesion, aggregation, release, fusion, and procoagulant activity. EDTA prevents platelets from clumping, so it is used as an anticoagulant in the platelet count. Excess concentration of K3EDTA causes shrinkage of blood cells. This study aimed to determine the difference in the number of platelets using K3EDTA anticoagulant with different sample volumes at the Wanadadi 1 Health Center employees, Kab. Banjarnegara. The study was conducted by analytical observation from February August 2022. A total of 10 respondents took 5 ml of blood samples and then divided them into K3EDTA vacutubes with sample volume of 0.5 ml, 1.5 ml, and 2.5 ml. Sample examination using the Hematology Analyzer impedanceelektrik method. The type of research design is analytic observational with a cross-sectional design. Random sampling technique. Data analysis was carried out by conducting a normality test. If the data were normally distributed, p 0.05, then the One Way ANOVA parametric test was continued. The mean number of platelets in a sample volume of 0.5 ml is 287,1000 31,14643 mm, the average number of platelets in a sample volume of 1.5 ml is 294,6000 34.67692 mm, and the average number of platelets in a sample volume of 2.5 ml of 291.1000 35.41955 mm. The lowest mean platelet count was at a volume of 0.5 ml based on statistical tests p = 0.885 (P 0.005). So, there is no significant difference in the number of platelets using K3EDTA Anticoagulants with different sample volumes for employees of Wanadadi Health Care Center 1 Banjarnegara.